Genome-wide association study reveals a GLYCOGEN SYNTHASE KINASE 3 gene regulating plant height in Brassica napus - Zhao, Chuanji; Yang, Li; Tang, Minqiang; Liu, Lijiang; Huang, Junyan; Tong, Chaobo; Xiang, Yang; Liu, Shengyi; Cheng, Xiaohui; Xie, Meili (Frontiers in Plant Science, 2022)
Rapeseed (Brassica napus) is an allotetraploid crop that is the main source of edible oils and feed proteins in the worldwide. The ideal plant architecture breeding is a major objective of rapeseed breeding and determining the appropriate plant height is a key element of the ideal plant architecture. Therefore, this study aims to improve the understanding of the genetic controls underlying plant height. The plant heights of 230 rapeseed accessions collected from different growing regions around the world were measured in field experiments over two consecutive years in Wuhan, China. All accessions were genotyped using whole-genome resequencing and 1,707,194 informative single nucleotide polymorphisms were acquired and used for genome-wide association analysis (GWAS). GWAS and haplotype analysis showed that BnaA01g09530D, which encodes BRASSINOSTEROID-INSENSITIVE 2 and belongs to the GLYCOGEN SYNTHASE KINASE 3 (GSK3) family, was significantly associated with plant height in B. napus. A total of 31 BnGSK3s with complete domains were identified and clustered into four groups according to phylogenetic analysis, gene structure, and motif distribution. The expression patterns showed that BnGSK3s exhibited significant differences in 13 developmental tissues in B. napus, suggesting that BnGSK3s may be involved in tissue-specific development. Sixteen BnGSK3 genes were highly expressed the in shoot apical meristem, which may be related to plant height or architecture development. These results are important for providing new haplotypes of plant height in B. napus and for extending valuable genetic information for rapeseed genetic improvement of plant architecture.